Evaluation of maize inbred lines currently used in Chinese breeding programs for resistance to six foliar diseases - Xiaoming Wang; Yunhua Zhang; Xiude Xu; Hongjie Li; Xiaofei Wu; Shihuang Zhang; Xinhai Li (Crop Journal, 2014)
Foliar diseases are common in most maize-producing regions and have caused serious yield reduction in China. To evaluate genetic resistance of parental lines actively used in maize breeding programs to major foliar diseases, 152 maize inbred lines were tested against northern corn leaf blight (NCLB), southern corn leaf blight (SCLB), Curvularia leaf spot (CLS), gray leaf spot (GLS), common rust, and southern rust from 2003 to 2005. A small number of lines exhibited highly resistant reactions to common rust and southern rust, but none were highly resistant to NCLB, SCLB, CLS, and GLS. Although 53.3%, 40.8%, and 80.7% of lines were resistant to NCLB, SCLB, and common rust, the resistance in most lines was moderate. Resistance to CLS, GLS, and southern rust was rare in this collection of maize lines. Five lines, 313, Chang 7-2, Qi 319, Qi 318, and Shen 137, were resistant to five diseases tested. Lines belonging to heterotic subgroup PB exhibited better resistance to the foliar diseases than lines from other heterotic subgroups, such as BSSS, PA, Lancaster, LRC, and PA. The results will be of benefit to breeders for selecting lines in disease resistance breeding programs.